SYNTHESIS AND CHARACTERIZATION OF LiFePO4/PPy/CLAY COMPOSITE AS CATHODE MATERIAL FOR Li-ION BATTERY - Indra Gunawan; Yustinus P; Sudaryanto Sudaryanto; Jadigia Ginting (Jurnal Sains Materi Indonesia, 2020)
SYNTHESIS AND CHARACTERIZATION OF LiFePO4/PPy/CLAY COMPOSITE AS CATHODE MATERIAL FOR Li-ION BATTERY. Conductor polymers have been used previously as a conducting agent or carbon source in various sol-gel and solid state methods to increase the conductivity of LiFePO4. The composite of LiFePO4/PPy/Clay were synthesized by mixing LiFePO4 and clay with a Ppy solution. The characterizations were done by using X-Ray Diffractometer (XRD), Scanning Electron Microscope (SEM) and LCR meter respectively. From XRD analysis it could be deduced that LiFePO4 has an ordered olivine structure with a Pnma space group. The SEM images provide clear evidence that small crystal particles of LiFePO4 either coat the surface of the clay particles or lie among them. These LiFePO4 particles have a small particle size (100–500 nm). With the increasing of LiFePO4 content, these small crystal particles at the surface or among the clay particles are increased. Increasing the PPy content to increase the conductivity of the material obtained. With the addition of clay from 5 to 10 wt. %, the DC conductivity of the blends is clearly observed to increase up to three orders of magnitude.